Evaluation of physico-chemical factor interactions in the cryopreservation of Paracentrotus lividus pluteus larvae - Lago, Alba; Paredes, Estefanía (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):295